2012
DOI: 10.1111/rda.12014
|View full text |Cite
|
Sign up to set email alerts
|

Golgi Apparatus and Endoplasmic Reticulum Dynamic during Meiotic Development in Canine Oocytes

Abstract: ContentThe Golgi apparatus (GA) and endoplasmic reticulum (ER) play a central role in the events related to intracellular trafficking distribution. This work evaluated the dynamics and localization of the GA and ER in canine oocytes during meiotic development in vitro. Cumulus-oocytes complexes (COCs) from ovaries of adult bitches were incubated for IVM for 0, 48, 72 and 96 h. At each time, the nuclear status was determined using DAPI staining, and the GA was evaluated by immunofluorescence using two antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Therefore, based on the results of ER distribution and function, we investigated the effect of HT exposure on distribution and function of the Golgi apparatus. Normally, the Golgi apparatus is fragmented and dispersed in the cortical area in canine MII oocytes (De los Reyes et al, 2012). The number of Golgi apparatus membranous vesicles in the cortex increases following oocyte maturation in mouse oocytes (Ducibella et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, based on the results of ER distribution and function, we investigated the effect of HT exposure on distribution and function of the Golgi apparatus. Normally, the Golgi apparatus is fragmented and dispersed in the cortical area in canine MII oocytes (De los Reyes et al, 2012). The number of Golgi apparatus membranous vesicles in the cortex increases following oocyte maturation in mouse oocytes (Ducibella et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Following oocyte maturation, ER is redistributed and localized in the cortex, and forms clusters, which are usually 1-2 mm in diameter (Kline, 2000). Localization of ER clusters is analogous to the distribution of polarized CGs (Kline, 2000), and is essential for preparing oocytes for the generation of rapid calcium waves, which induce oocyte activation during fertilization (De los Reyes et al, 2012). Previous studies have suggested that citrinin exposure increases abnormal ER distribution in mice (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulus oocytes complexes from all six groups were subjected to IVM at 38°C, 5% CO 2 and saturated humidity for 72 hr (De los Reyes, Palomino, Jofré, Villarroel, & Moreno, ). Experiments were conducted using 100 μl droplets of each medium covered with mineral oil (Sigma), each containing no more than eight COCs.…”
Section: Methodsmentioning
confidence: 99%
“…Cell organelles including mitochondria, the endoplasmic reticulum (ER), and microtubules play important roles in both nuclear and cytoplasmic maturation through the regulation of protein and ATP synthesis and chromosome segregation ( Mao et al, 2014 ). However, inadequate in vitro conditions lead to the abnormal behavior of cell organelles and finally result in disrupted meiotic maturation ( Ueno et al, 2005 ; De los Reyes et al, 2011 ; De los Reyes et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%